Attitudes of Doctors and Nurses toward the Chronic Care Model - Rolando Bonal Ruiz; Meibis Poll Cabrera (Revista Finlay)
Background: the fact that chronic diseases replace traditional causes of morbidity and mortality in a country, or are on a par with major common health problems, demands the development of new strategies to address them. Objective: to explore attitudes of doctors and nurses from the Rolando López Peña Polyclinic toward the Chronic Care Model. Methods: a quantitative and qualitative cross-sectional study was conducted including the 22 family physicians and 26 nurses who provide care to patients with chronic diseases and were at the polyclinic at the time of the study. All were administered a 5 point Likert scale and a focus group interview, which was taped, transcribed and analyzed. Results: the attitudinal results correspond with the actions assessed in each component of the model, being the most common barriers: the lack of awareness and training on the new approaches to care of these patients, work overload created by other programs such as the maternal-child and vector control programs, uncertainties on the effectiveness of patient education and ignorance of the practice guidelines. Conclusions: favorable attitudes toward the introduction of the model to the practice of the family physician and nurse predominated as long as organizational changes are made and the suggestions of these service providers are put into practice with the support of the decision makers of the health sector.